Identification of a Drosophila Myb-E2F2/RBF transcriptional repressor complex - Lewis, Peter W. (Cold Spring Harbor Laboratory Press, 2004)
The Drosophila Myb complex has roles in both activating and repressing developmentally regulated DNA replication. To further understand biochemically the functions of the Myb complex, we fractionated Drosophila embryo extracts relying upon affinity chromatography. We found that E2F2, DP, RBF1, RBF2, and the Drosophila homolog of LIN-52, a class B synthetic multivulva (synMuv) protein, copurify with the Myb complex components to form the Myb-MuvB complex. In addition, we found that the transcriptional repressor protein, lethal (3) malignant brain tumor protein, L(3)MBT, and the histone deacetylase, Rpd3, associated with the Myb-MuvB complex. Members of the Myb-MuvB complex were localized to promoters and were shown to corepress transcription of developmentally regulated genes. These and other data now link together the Myb and E2F2 complexes in higher-order assembly to specific chromosomal sites for the regulation of transcription.